70 years of decoloniality: epistemic disobedience and global public health - McGovern, Justine; Fusco, Lisa (Frontiers in Public Health, 2025)
The term “epistemic disobedience” was coined by Walter Mignolo in his 2009 article entitled Epistemic Disobedience, Independent Thought and De-Colonial Freedom. While the decolonialization of global health research and practice has gained traction, epistemic disobedience is an emergent perspective in scholarship occurring at the intersection of public health and the population movement. Linked to decoloniality, a practice that coalesced in 1955, epistemic disobedience refers to research practices and perspectives that dismantle the power dynamics of colonialism by de-linking geopolitics from knowledge building (Mignolo, 2009). This mini review defines and situates key terms in historical and current literature; critically explores the usage of epistemic disobedience in public health scholarship; draws on case examples to suggest ways to apply epistemic disobedience; and articulates applications and implications in public health research and practice that seek to increase health equity as a human right.